Editorial - Tatnall , Arthur (Journal of Law and Governance, 2008)
This final issue (Number 4) for 2008 of Volume 3 of the Journal of Business Systems, Governance and Ethics contains a range of articles from Australia, Sweden, USA, Malaysia and the United Arab Emirates.